Topological Optimization of a Supporting Part of a 3D Printer Pad - Pollak, Martin; Kascak, Jakub; Torokova, Monika; Kocisko, Marek; Dobransky, Jozef (Manufacturing Technology Journal, 2020)
Generative design is one of the most promising means of new product development in the world. It allows formation of organic structures that brings various benefits, e.g. in the form of savings of material and production costs. Generative design includes several types of technology, topological optimization included. The paper addresses the technology of topological optimization implemented on the support part of the 3D printing pad. The result of optimization is the creation of a new, more suitable design concept through the Altair Inspire optimization software.
Keywords: Generative design; Topological optimization; Additive technology; FFF/FDM technology; Altair Inspire software